TANGGAPAN PENGUNJUNG TERHADAP ATRAKSI WISATA DI SKYWALK TENGKU BUANG ASMARA KABUPATEN SIAK - ', Poppy; Sidiq, Rd Siti Sofro (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2025)
This research was conducted to analyze visitor responses to tourist attractions at the Tengku Buang Asmara Skywalk with a focus on four main dimensions: Uniqueness, Authenticity, Rarity, Benefits for Tourists. The method used is descriptive quantitative, with data collected through observation, questionnaires and documentation. A total of 100 respondents, who were visitors to the Tengku Buang Asmara Skywalk, were involved in this research. The research results show that visitors agree with the indicators. The uniqueness of natural beauty, the uniqueness of artificial beauty, the originality of the place, the authenticity of tourist attractions, the scarcity of tourist attractions, providing pleasure, providing comfort are the main attractions at the Tengku Buang Asmara Skywalk. However, even though visitors agree with the tourist attractions at the tourist attraction, they still have to maintain the existing tourist attractions, if necessary, add new tourist attractions so that visitors are interested in coming back. In conclusion, visitors agree with the attractions of the Tengku Buang Asmara Skywalk. The implementation of these suggestions is expected to increase the number of visits to the Tengku Buang Asmara Skywalk Tourist Attraction. Keywords: Visitor Responses, Tengku Buang Asmara Skywalk, Tourist Attractions